Prevention of spontaneous preterm birth: Guidelines for clinical practice from the French College of Gynaecologists and Obstetricians (CNGOF). (March 2017) - Sentilhes, Loïc; Sénat, Marie-Victoire; Ancel, Pierre-Yves; Azria, Elie; Benoist, Guillaume; Blanc, Julie; Brabant, Gilles; Bretelle, Florence; Brun, Stéphanie; Doret, Muriel; Ducroux-Schouwey, Chantal; Evrard, Anne; et al.
Abstract: In France, 60, 000 neonates are born preterm every year (7.4%), half of them after the spontaneous onset of labor. Among preventable risk factors of spontaneous prematurity, only cessation of smoking is associated with decreased prematurity (level of evidence [LE]1). It is therefore recommended (Grade A). Routine screening and treatment of vaginal bacteriosis is not recommended in the general population (Grade A). The only population for which vaginal progesterone is recommended is that comprising asymptomatic women with singleton pregnancies, no history of preterm delivery, and a short cervix at 16–24 weeks of gestation (Grade B). A history-indicated cerclage is not recommended for women with only a history of conization (Grade C), uterine malformation (professional consensus), isolated history of preterm delivery (Grade B), or twin pregnancies for primary (Grade B) or secondary (Grade C) prevention of preterm birth. A history-indicated cerclage is recommended for a singleton pregnancy with a history of at least 3 late miscarriages or preterm deliveries (Grade A). Ultrasound cervical length screening is recommended between 16 and 22 weeks for women with a singleton previously delivered before 34 weeks gestation, so that cerclage can be offered if cervical length <25 mm before 24 weeks (Grade C). A cervical pessary is not recommended for the prevention of preterm birth in a general population of asymptomatic women with twin pregnancies (Grade A) or in populations of asymptomatic women with a short cervix (professional consensus). Although the implementation of universal screening by transvaginal ultrasound for cervical length at 18–24 weeks of gestation in women with a singleton gestation and no history of preterm birth can be considered by individual practitioners, this screening cannot be universally recommended. In cases of preterm labor, (i) it is not possible to recommend any one of the several methods (ultrasound of the cervical length, vaginal examination, or fetal fibronectin assay) over any other to predict preterm birth (Grade B); (ii) routine antibiotic therapy is not recommended (Grade A); (iii) prolonged hospitalization (Grade B) and bed rest (Grade C) are not recommended. Compared with placebo, tocolytics are not associated with a reduction in neonatal mortality or morbidity (LE2) and maternal severe adverse effects may occur with all tocolytics (LE4). Atosiban and nifedipine (Grade B), unlike beta-agonists (Grade C), can be used for tocolysis in spontaneous preterm labor without preterm premature rupture of membranes. Maintenance tocolysis is not recommended (Grade B). Antenatal corticosteroid administration is recommended for all women at risk of preterm delivery before 34 weeks of gestation (Grade A). After 34 weeks, the evidence is insufficiently consistent to justify recommending systematic antenatal corticosteroid treatment (Grade B), but a course of this treatment might be indicated in clinical situations associated with high risk of severe respiratory distress syndrome, mainly in case of planned cesarean delivery (Grade C). Repeated courses of antenatal corticosteroids are not recommended (Grade A). Rescue courses are not recommended (Professional consensus). Magnesium sulfate administration is recommended for women at high risk of imminent preterm birth before 32 weeks (Grade A). Cesareans are not recommended for fetuses in vertex presentation (professional consensus). Both planned vaginal and elective cesarean delivery are possible for breech presentations (professional consensus). Delayed cord clamping may be considered if the neonatal or maternal state allows (professional consensus).